Terlipressin versus placebo or noradrenalin in the treatment of hepatorenal syndrome: a systematic review and meta-analysis - Yue-Meng Wan; Song-Quan Huang; Hua-Mei Wu; Yu-Hua Li; Hong-Jing Yin; Ying Xu (Frontiers Media S.A., 2024)
BackgroundHepatorenal syndrome (HRS) bears a very poor prognosis with unmet need for safe and effective therapies. This systematic review and meta-analysis aimed to re-assess safety and efficacy of terlipressin versus placebo or noradrenaline for HRS, based on previous randomized controlled trials (RCTs).MethodsPubMed, EMBASE, MEDLINE (OvidSP) and Cochrane registers were searched for trials reporting HRS treatment by terlipressin or noradrenaline. Search terms included: "hepatorenal syndrome", "terlipressin", "noradrenaline", and corresponding synonyms. Comparisons between terlipressin, noradreanaline, placebo and albumin were included. Meta-analysis was conducted for treatment response (both HRS reversal and complete response), mortality and adverse events.Results15 RCTs were included, enrolling 1236 HRS patients (type 1: 1166, type 2: 70). Treatment with terlipressin+albumin resulted in significantly higher treatment response than placebo+albumin or albumin alone (risk ratio [RR]:2.75, 95% confidence interval [CI]:1.96 to 3.84; I2 = 28%, p = 0.23; n = 6). Noradrenaline was equally effective in treatment response compared to terlipressin (RR:1.19, 95% CI:0.96 to 1.46; I2 = 16%, p = 0.31; n = 7), but trials were limited by its non-blind design and small size. Sensitivity analysis showed no survival benefit with terlipressin compared to either placebo (RR:1.03, 95% CI:0.83 to 1.28; I2 = 0%, p = 0.72; n = 3) or noradreanline (RR:0.83, 95% CI:0.69 to 1.00; I2 = 4%, p = 0.39; n = 7) at 30 days of follow-up. Terlipressin carried higher risk of treatment-related adverse events compared to either placebo (RR:2.92, 95% CI:1.48 to 5.77; I2 = 0%, p = 0.75; n = 3) or noradrenaline (RR:2.45, 95% CI:1.37 to 4.37; I2 = 0%, p = 0.92; n = 5).ConclusionTerlipressin is superior to placebo, and comparable to noradreanline in treatment response, but survival benefit is lacking. Noradrenaline, with low certainty, may be a better alternative for HRS.